TEACHING READING USING THE REAP (READING, ENCODE, ANNOTATE AND PONDER) STRATEGY IN READING COMPREHENSION - Nelvia Ibrahim (Bajang Institute, 2024)
This article aims to explain the use of the REAP strategy in teaching reading. There are so many teaching reading strategies that the teacher has applied for different reading purposes. Meanwhile, it helps the readers achieve their purposes in reading. Utilizing the Read, Encode, Annotate and Ponder (REAP) strategy. It was supposed that Read, Encode, Annotate, Ponder (REAP) was appropriate for overcoming the problem. The method used in this research is the students should have also it should be support by their comprehension moreover, reading without comprehension is really difficult to understand about something that has been appear in the magazines, newspapers, books or other the printed materials eventhogh it was fiction or non fiction